Karakteristik gambaran Tuberkulosis (TB) paru pada foto toraks pasien Human Immunodeficiency Virus (HIV) tahun 2017-2021 di RSUP Sanglah, Bali, Indonesia - Tiffany Rebecca; Dewa Gde Mahiswara Suadiatmika; Ni Nyoman Margiani (DiscoverSys Inc., 2021)
Background: Tuberculosis is a disease caused by Mycobacterium tuberculosis that mostly attacks the lungs. HIV is a virus that causes damage to the immune system. HIV infection increases the risk of developing pulmonary TB because TB is an opportunistic disease; vice versa TB infection increases HIV progression. This study is about researching the characteristics of TB in HIV patients radiologically at Sanglah Hospital Denpasar.Methods: This study is a cross-sectional descriptive study conducted retrospectively. The data in this study used medical records of HIV-infected pulmonary TB patients from Sanglah Hospital, especially the characteristics of chest radiographs in the medical records and chest X-rays of patients. For the data collecting technique, a total sample is used to analyze all 47 cases. Data were analyzed using SPSS version 25 for Windows.Results: Most HIV patients with pulmonary TB coinfection at Sanglah Hospital, Denpasar, were obtained from as many as 47 people. It was found that the age between 30 - 39 recorded to be the highest at 31.3%, men were the most dominant with 81.3%, most of the patients diagnosed with HIV stage 4 were 72.9%, and the most dominant characteristics of the chest radiograph are 41.7% consolidation.Conclusion: Most cases of pulmonary TB with HIV coinfection at Sanglah Hospital Denpasar in 2017 - 2021 are male around 30 - 39 years. In addition, most of them were diagnosed with HIV stage 4 and finally almost all the patients had consolidation characteristics on chest radiographs. Latar Belakang: Tuberkulosis adalah penyakit yang disebabkan oleh Mycobacterium tuberculosis yang paling banyak menyerang paru-paru. HIV adalah virus yang menyebabkan kerusakan pada sistem kekebalan tubuh. Infeksi HIV meningkatkan risiko berkembangnya TB paru karena TB adalah penyakit oportunistik sebaliknya infeksi TB meningkatkan perkembangan HIV. Penelitian ini bertujuan untuk mengetahui karakteristik TB pada pasien HIV secara radiologis di RSUP Sanglah Denpasar.Metode: Penelitian ini merupakan penelitian deskriptif potong lintang yang dilakukan secara retrospektif. Data dalam penelitian ini menggunakan rekam medis pasien TB paru terinfeksi HIV dari RSUP Sanglah, terutama karakteristik foto toraks pada rekam medis dan foto rontgen dada pasien. Untuk teknik pengumpulan data, sampel total digunakan untuk menganalisis semua 47 kasus. Data dianalisis dengan SPSS versi 25 untuk Windows.Hasil: Pasien HIV koinfeksi TB paru terbanyak di RS Sanglah Denpasar didapatkan sebanyak 47 orang. Didapatkan usia antara 30-39 tahun tercatat paling tinggi 31,3%, laki-laki paling dominan dengan 81,3%, sebagian besar pasien terdiagnosis HIV stadium 4 sebanyak 72,9%, dan karakteristik foto toraks yang paling dominan adalah konsolidasi 41,7%.Kesimpulan: Kasus TB paru koinfeksi HIV terbanyak di RSUP Sanglah Denpasar tahun 2017 – 2021 adalah laki-laki berusia sekitar 30–39 tahun. Selain itu, sebagian besar terdiagnosis HIV stadium 4 serta hampir semua pasien memiliki karakteristik konsolidasi pada radiografi dada.